Internalisasi Nilai Moderasi Beragama pada Masyarakat Multikultural - Fathurrohman, Fathurrohman (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
This study aims to discuss the internalization of the value of religious moderation in a multicultural society. This study uses a qualitative approach and data processing using a descriptive-analytical method. The results and discussion of this study indicate that there are several ways that can be used to internalize the value of religious moderation in a multicultural society. This study concludes that the internalization of the value of religious moderation in a multicultural society can be done in various ways. An important effort to internalize religious moderation in a multicultural society is to strengthen tolerance among religious people.